The six-year prevalence of Crimean-Congo Hemorrhagic Fever (CCHF) in Erzurum, Turkey - Hakan Igan; Hayrunisa Hanci (Journal of Vector Borne Diseases)
Background & objectives: Crimean-Congo Hemorrhagic Fever (CCHF) is a potentially deadly viral disease and Turkey is the country in which the disease is seen the most. The purpose of this study is to estimate the frequency and case fatality ratio (CFR) of CCHF disease in Erzurum/Turkey between 2015-2021. Methods: The CCHF positivity in patients was detected on serum samples via RT-PCR method with RNA detection. Demographic data belonging to positive patients, such as, age, gender, region of residence, tick contact was analyzed retrospectively. Results: It was detected that the RT-PCR test of 521 patients out of total 1378 sent to the laboratory were positive. Each sample belonged to a single patient and repeating samples were left out of the study. The year with least positive patient ratio in relation to potential CCHF positive samples was 2017 (21.12%) whereas the year with the most positivity ratio was 2020 (55.48%). The case fatality ratio in the six-year period was calculated to be 1.34%. Interpretation & conclusion: This study has demonstrated that there is a significant rise in CCHF patients, especially in 2020 when the COVID-19 pandemic began. In order to prevent this rise, it is crucial that the effect of the COVID-19 pandemic on increased interactions of humans with ticks is researched thoroughly, a biological intervention is made and public awareness on CCHF disease is increased.